Using Kamishibai Media in Thematic Learning to Increase Students' Knowledge of Environmental Education - Indriyani Rachman; Wati Rohmawatiningsih; Kodama Yayoi (Universitas Diponegoro, 2021)
Global environmental damage emphasizes the importance of environmental education at schools. It is a tool for achieving sustainable development. Environmental education (EE) is integrated into several core subjects in the Indonesian primary school curriculum as a thematic learning. For the teachers, it is essential to be aware of planning and designing appropriate learning methods based on the physical, emotional, and cognitive stages primary students. Kamishibai seems suitable for EE learning at primary school. It can help students to understand EE content. The aim of this study was to analyze using Kamishibai in thematic learning to increase the students' knowledge of EE. The method used in this study was pre-experiment with the research design of the one-group pretest-posttest design. Nine 5th grade students participated in the study. To determine the students’ knowledge of EE, a test was administered before and after the Kamishibai implementation. As a result of the analysis, it was found that, after the implementation, the students’ knowledge of EE was higher than before implementation. The result also showed the students’ ability in retelling the story at the end of the Kamishibai implementation. These indicated that Kamishibai strengthened students' memory. In conclusion, Kamishibai increased students' knowledge of EE.